2005
DOI: 10.1186/1477-7525-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the UK-English version of the Pediatric Quality of Life Inventory™ 4.0 (PedsQL™) generic core scales

Abstract: BackgroundHealth related quality of life (HRQL) has been recognised as an important paediatric outcome measurement. One of the more promising measures to emerge in recent years is the Pediatric Quality Of Life Inventory (PedsQL™), developed in the US. Advantages of the PedsQL™ include brevity, availability of age appropriate versions and parallel forms for child and parent. This study developed a UK-English version of PedsQL™ generic module and assessed its performance in a group of UK children and their paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
68
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(91 citation statements)
references
References 21 publications
15
68
3
3
Order By: Relevance
“…These results emphasise the need for addressing the issue of diagnosis and presence of late effects in QoL studies in childhood cancer survivors. Our results are consistent with other studies of reduced QoL among children surviving brain tumours (Upton et al, 2005;Cardarelli et al, 2006;Varni et al, 2007;Penn et al, 2009;Yoo et al, 2010), as well as among studies and reviews of late effects and QoL of childhood cancer (Pemberger et al, 2005;Calaminus et al, 2007;Eiser et al, 2007;Ishida et al, 2010a, b).…”
Section: Child and Parent Proxy Reportssupporting
confidence: 93%
“…These results emphasise the need for addressing the issue of diagnosis and presence of late effects in QoL studies in childhood cancer survivors. Our results are consistent with other studies of reduced QoL among children surviving brain tumours (Upton et al, 2005;Cardarelli et al, 2006;Varni et al, 2007;Penn et al, 2009;Yoo et al, 2010), as well as among studies and reviews of late effects and QoL of childhood cancer (Pemberger et al, 2005;Calaminus et al, 2007;Eiser et al, 2007;Ishida et al, 2010a, b).…”
Section: Child and Parent Proxy Reportssupporting
confidence: 93%
“…The presence of a relation between the dimensions of Peds 4.0 and the sociodemographic and clinical parameters is an important finding as such instruments could be used in therapeutic evaluations (Upton et al, 2005;Ware, 1997;Dean et al, 2010). Our results are in contrast with other results that have failed to observe gender differences (Varni et al, 2007;Varni et al, 2003) or found fewer negative associations (Reinfjell et al, 2006;Villalonga-Olives et al, 2010).…”
Section: Discussioncontrasting
confidence: 56%
“…This was also observed for Lebanese people aged 14 year and more using the SF-36 Health survey (Sabbah et al, 2003), which could be due to factors such as stress, morbidity of the parents (Duhamel, 2007), war status, lack of health coverage (Sabbah et al, 2007), lack of public green spaces (Costa, Vescina, & Barcellos Pinheiro, 2010), and comorbidities (Sabbah et al, 2003;Varni et al, 2003;Upton et al, 2005). Additionally, the physical functioning of children is low.…”
Section: Cancer Childmentioning
confidence: 98%
See 1 more Smart Citation
“…The reliability of the UK version of the PedsQL was also assessed in a sample of 1399 children and 970 parents from south Wales, and was shown to have similar internal reliability with all subscales on both the child and parent reports, reaching α = 0.70 (minimum standard) and exceeded α = 0.90 for the total score. 47 They recommend the UK version of the PedsQL for assessment of quality of life in UK children.…”
Section: Physical and Mental Healthmentioning
confidence: 99%